Nonlinear screening designs for defense testing: an overview and case study. (July 2015) - Dougherty, Shane; Simpson, James R; Hill, Raymond R; Pignatiello, Joseph J; White, Edward D
Recent efforts to improve the statistical rigor of both developmental and operational testing include recommendations to consider second-order screening designs. In this paper, we provide a broad review of screening designs and second-order screening designs. We then consider a real-world wind tunnel experiment case study from the recent published literature and use subject matter expertise to consider the viability of second-order screening design, a recently developed design called the DSD+, to sufficiently screen important factors in complex, nonlinear systems of interest using just a single experimental design.